Peran Struktur Modal dalam Meningkatkan Nilai Perusahaan pada BPR - Wita Retenia Gulo; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the role of capital structure in the management and enhancement of firm value in Rural Banks (Bank Perkreditan Rakyat/BPR) in Bawen, Semarang Regency. The study focuses on how capital structure is understood, formulated, and implemented by BPR management as a strategic policy to maintain operational stability, ensure compliance with banking regulations, and support long-term business sustainability. To address this issue, capital structure theories, particularly the trade-off theory and signalling theory, are employed to explain managerial considerations in financing decisions. Data were collected through in-depth interviews, observation, and documentation, and were analysed qualitatively using a thematic approach. The findings indicate that capital structure in BPR is implemented conservatively by emphasising core capital adequacy and prudent management of third-party funds, in line with the institution’s risk profile and regulatory requirements. A sound capital structure indirectly enhances firm value by strengthening customer trust, reinforcing institutional reputation, and fostering positive perceptions of bank soundness. This study highlights a theoretical contribution by demonstrating that the application of capital structure theories in BPR is contextual and largely influenced by regulatory factors and local characteristics, thus differing from large-scale corporate practices. The novelty of this research lies in revealing the role of capital structure as a trust-based strategic mechanism in enhancing firm value in locally scaled banking institutions.